Angiotensin II constricts mouse iliac arteries: possible mechanism for aortic aneurysms - Gadanec, Laura Kate; McSweeney, Kristen Renee; Kubatka, Peter; Caprnda, Martin; Gaspar, Ludovit; Prosecky, Robert; Dragasek, Jozef; Kruzliak, Peter; Apostolopoulos, Vasso; Zulli, Anthony (Molecular and cellular biochemistry, 2024)
Abdominal aortic aneurysms (AAA) result from maladaptive remodeling of the vascular wall and reduces structural integrity. Angiotensin II (AngII) infusion has become a standard laboratory model for studying AAA initiation and progression. We determined the different vasoactive responses of various mouse arteries to Ang II. Ex vivo isometric tension analysis was conducted on 18-week-old male C57BL/6 mice (n = 4) brachiocephalic arteries (BC), iliac arteries (IL), and abdominal (AA) and thoracic aorta (TA). Arterial rings were mounted between organ hooks, gently stretched and an AngII dose response was performed. Rings were placed in 4% paraformaldehyde for immunohistochemistry analysis to quantify peptide expression of angiotensin type 1 (AT1R) and 2 receptors (AT2R) in the endothelium, media, and adventitia. Results from this study demonstrated vasoconstriction responses in IL were significantly higher at all AngII doses when compared to BC, and TA and AA responses (maximum constriction-IL: 68.64 ± 5.47% vs. BC: 1.96 ± 1.00%; TA: 3.13 ± 0.16% and AA: 2.75 ± 1.77%, p < 0.0001). Expression of AT1R was highest in the endothelium of IL (p < 0.05) and in the media and (p < 0.05) adventitia (p < 0.05) of AA. In contrast, AT2R expression was highest in endothelium (p < 0.05), media (p < 0.01, p < 0.05) and adventitia of TA. These results suggest that mouse arteries display different vasoactive responses to AngII, and the exaggerated response in IL arteries may play a role during AAA development.
Keywords: Angiotensin I; Aortic Aneurysm; arteria iliaca; aortální aneurysma; Angiotensin II; angiotensin II; aneurysma břišní aorty; zvířata; myši; peptidové hormony; myši inbrední C57BL; Aortic Aneurysm, Abdominal; Mice; Peptide Hormones; arterie; Arteries; Male; Mice, Inbred C57BL; Animals; mužské pohlaví; Iliac Artery; angiotensin I